2006
DOI: 10.1007/s00244-004-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River

Abstract: This study determined the partitioning of total mercury in liver, gonad, and cheek muscle of white sturgeon (Acipenser transmonatus) in the lower Columbia River. The relationship between tissue mercury concentrations and various physiologic parameters was assessed. White sturgeon were captured in commercial fisheries in the estuary and Bonneville, The Dalles, and John Day Reservoirs. Condition factor (CF), relative weight (Wr), and gonadosomatic index (GSI) were determined for each fish (n = 57). Gonadal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Therefore, to examine the extent of heavy metal exposure on sex hormones in fishes from the Kor River, we assayed three important steroid hormones in both sexes. Estradiol concentrations in female fish in the heavily polluted area (middle sampling site) were significantly lower than at the other two sampling sites; this result shows a direct effect of metal contamination on steroidogenesis in female fish, which could be due to the harmful effects of metals on either the hypothalamus-pituitary axis (Kime 1995;Kime et al 2001;Song et al 2002) or on the germinal cells capacity of estradiol production (Drevnick and Sandheinrich 2003;Hinck et al 2007;Kime 1995;Webb et al 2006). In male fish; the concentration of testosterone hormone from samples from the control site (Doroudzan Dam) was higher than that of the two other areas.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, to examine the extent of heavy metal exposure on sex hormones in fishes from the Kor River, we assayed three important steroid hormones in both sexes. Estradiol concentrations in female fish in the heavily polluted area (middle sampling site) were significantly lower than at the other two sampling sites; this result shows a direct effect of metal contamination on steroidogenesis in female fish, which could be due to the harmful effects of metals on either the hypothalamus-pituitary axis (Kime 1995;Kime et al 2001;Song et al 2002) or on the germinal cells capacity of estradiol production (Drevnick and Sandheinrich 2003;Hinck et al 2007;Kime 1995;Webb et al 2006). In male fish; the concentration of testosterone hormone from samples from the control site (Doroudzan Dam) was higher than that of the two other areas.…”
Section: Discussionmentioning
confidence: 70%
“…We found that the prevalence of MAs in tissues, liver size (LSI), and condition were positively related to tissue Hg concentrations. These latter two relationships were unexpected given the negative relationships reported between fish tissue Hg concentrations and LSI [16], and condition (e.g., [9,10]) in fish with lower tissue Hg concentrations than those in perch from KNPNHS. Despite the elevated Hg concentrations in perch from the present study, evidence of adverse health effects due to Hg were only found at the cellular level.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, condition was negatively related to whole-body (THg) in yearling yellow perch ($0.03-0.23 mg g À1 wet wt) [40], to muscle (THg) in wild walleye ($0.20-0.38 mg g À1 wet wt) [6], to liver (THg) in northern pike (0.07-0.62 mg g À1 wet wt in muscle) [14], to liver and gonad (THg) in white sturgeon (Acipenser transmontanus; 0.020-0.780 mg g À1 wet wt in liver) [10], and to liver, muscle, and blood (THg) in striped bass (Morone saxatilis; 0.06-1.06 mg g À1 wet wt in muscle) [9]. The relationship between MeHg and fish condition can be confounded by relationships between condition and fish age in some field studies [41], and a weak positive relationship existed in the present study between perch condition and age.…”
Section: Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used data from white sturgeon in the lower Columbia River to estimate Q. Mercury concentrations in white sturgeon were significantly higher in muscle (170.54 ± 12.67 ppb, n = 57) and liver (140.26 ± 23.02 ppb, n = 49) than in gonadal tissue (27.26 ± 2.50 ppb, n = 49) (Webb et al 2006). Our estimate of Q = 0.16 for sturgeon is higher than the value of 0.12 estimated by Trudel and Rasmussen (2001) for fish in general.…”
Section: Mercury Redistributionmentioning
confidence: 99%